Brand Anarchy : Managing corporate reputation. - Waddington, Stephen (Bloomsbury Pub., 2012)
As the media landscape looks increasingly diverse and anarchic, individuals, organisations and governments should not waste time wondering whether they have lost control of their reputations. The simple fact is that they have never had control. The question is what they can do about it now, and what they need to consider for the future. The fragmentation of media and the rise of social media has brought brand and personal reputational risk into sharp focus like never before. Disaffected shareholders, customers and staff are voicing their opinions to a global internet audience. In a brand conte.